(untitled) (Philological Studies, 2023)
In addition to all their other efforts, the national revivalists tried to bring awareness of the importance of upbringing and education in terms of forming a young citizenship, aware of their affiliation. Many literary works speak of this, and one of them is „Confessions“ (1868) by Blaz Lorkovic, being the first Croatian episodic novel. It is a title that has been systematically ignored by older critics for a long time. The more recent studies advocate for its importance, considering it to be the best Romanesque text before Senoa’s appearance on the literary scene. Its significance in terms of the achievement of successful psychologization of the hero that was achieved by the epistolary form was particularly explored. This paper aims to show that the key for one of the possible interpretations of Lorkovic’s novel is in the upbringing. In that way we could perceive all the efforts of the Croatian revivalists in terms of creating critical masses that have resisted procreation. This is a prerequisite for the purpose of upbringing and education, which the author clearly advocates, and which, except in school settings, must be done and accomplished at home. In this regard, the leading role is attributed to women and mothers, with their role in affirmation of upbringing for values. Considering the connection between the moral and the social climax, one understands that an intentional moral upbringing is one of the preconditions for constituting nations.